A guide to conducting online research - Gaiser, Ted J.; Schreiner, Anthony E. (Los Angeles : SAGE, 2009)
This guide is designed to support students, academics and practition er researchers in using technology as part of their research.
Introduction -- Designing an online study -- Research standards and ethical considerations -- Using email for data collection -- Researchin g using instant messaging and chat -- Survey research on the Internet - - The world of Web 2.0: blogs, wikis and websites -- Accessing and usin g Web-based data -- Analyzing the data -- Emerging research opportuniti es -- Presenting your results -- Some additional challenges for online researchers -- Appendix 1 : Acronyms and jargon terms -- Appendix 2 : W eb links.
Includes bibliographical references (p. [168]-172) and index.
Keywords: Internet research; Internet searching; Research -- Methodology